Manajemen Data Real-Time Untuk Aplikasi Internet Of Things (IOT) - Mauli Fathia Zahra; Muhammad Irwan Padli Nasution (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Real-time data management plays a crucial role in Internet of Things (IoT) applications that require fast and efficient data processing and analysis. This article aims to explore various methods of real- time data management used in the context of IoT. These methods encompass data collection, transmission, storage, and real-time analytics. The primary focus is on enhancing the efficiency of IoT data management and minimizing delays in decision-making based on incoming data. The outcomes of this approach are expected to optimize the performance of IoT applications by providing rapid responsiveness to continuously flowing data. Thus, the article summarizes the objectives, methods, and outcomes of implementing real-time data management for high-performance and optimal responsiveness in IoT applications.